Vascular Smooth Muscle Cell Calcification Is Mediated by Regulated Exosome Secretion. Issue 8 (10th April 2015) - Kapustin, Alexander N.; Chatrou, Martijn L.L.; Drozdov, Ignat; Zheng, Ying; Davidson, Sean M.; Soong, Daniel; Furmanik, Malgorzata; Sanchis, Pilar; De Rosales, Rafael Torres Martin; Alvarez-Hernandez, Daniel; Shroff, Rukshana; Yin, Xiaoke; et al.
<x xml:space="preserve">Abstract</x> Rationale: Matrix vesicles (MVs), secreted by vascular smooth muscle cells (VSMCs), form the first nidus for mineralization and fetuin-A, a potent circulating inhibitor of calcification, is specifically loaded into MVs. However, the processes of fetuin-A intracellular trafficking and MV biogenesis are poorly understood. Objective: The objective of this study is to investigate the regulation, and role, of MV biogenesis in VSMC calcification. Methods and Results: Alexa488-labeled fetuin-A was internalized by human VSMCs, trafficked via the endosomal system, and exocytosed from multivesicular bodies via exosome release. VSMC-derived exosomes were enriched with the tetraspanins CD9, CD63, and CD81, and their release was regulated by sphingomyelin phosphodiesterase 3. Comparative proteomics showed that VSMC-derived exosomes were compositionally similar to exosomes from other cell sources but also shared components with osteoblast-derived MVs including calcium-binding and extracellular matrix proteins. Elevated extracellular calcium was found to induce sphingomyelin phosphodiesterase 3 expression and the secretion of calcifying exosomes from VSMCs in vitro, and chemical inhibition of sphingomyelin phosphodiesterase 3 prevented VSMC calcification. In vivo, multivesicular bodies containing exosomes were observed in vessels from chronic kidney disease patients on dialysis, and CD63 was found to colocalize with calcification. Importantly, factors such as tumor necrosis factor-α and platelet derived growth factor-BB were also found to increase exosome production, leading to increased calcification of VSMCs in response to calcifying conditions. Conclusions: This study identifies MVs as exosomes and shows that factors that can increase exosome release can promote vascular calcification in response to environmental calcium stress. Modulation of the exosome release pathway may be as a novel therapeutic target for prevention.